2S albumins and nsLTP are involved in anaphylaxis to pizza sauce: IgE recognition before and after allergen processing. (15th August 2020) - Martín-Pedraza, Laura; Wangorsch, Andrea; Bueno-Diaz, Cristina; de las Heras, Manuel; Scheurer, Stephan; Cuesta-Herranz, Javier; Villalba, Mayte
Highlights: Allergy to multi-ingredient dishes requires the identification of hidden allergens. 2S albumin and nsLTP allergens in pizza-allergic patients present limited cross-reactivity. Identify allergens underrepresented in extracts is essential to an accurate diagnosis. Reducing agents can mimic the allergenic epitope changes in industrial food processing. Abstract: Although pizza is one of the most popular foods in the world, allergic responses after ingesting pizza are relatively uncommon. However, precisely identifying the allergens responsible for these allergic reactions is challenging because of the high and diverse number of ingredients used in pizza preparation. In this report, we aim to identify the allergens responsible for systemic allergic reactions following ingestion of pizza in two patients. Using a skin prick by prick test (SPPT) and in vitro techniques, with natural and recombinant purified allergens from tomato and mustard seeds, we identified 2S albumin and non-specific lipid transfer proteins (nsLTP) as the proteins involved. However, IgE responses to the four nsLTPs differed before and after denaturation and reduction, thus suggesting additional complexity around nsLTP in food processing.